2014
DOI: 10.4236/jdm.2014.41007
|View full text |Cite
|
Sign up to set email alerts
|

Gait speed may predict development of Type 2 diabetes: A pilot study among elderly Japanese

Abstract: Aims: Epidemiologic evidence suggests that physical activity is associated with reduced risk of Type 2 diabetes. Walking is simple, effective, and by far the most prevalent physical activity among older adults. However, it is difficult to recognize and evaluate performance-based parameters of physical activity. The purpose of this study was to evaluate the importance of performance-based gait speed among several physical measurements in the development of Type 2 diabetes using long-term community-based data on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…The results also showed that slower gait speed (<1.32 m/s) was a significant predictor for incident DM in this population. These results were consistent with a previous study that examined baseline gait speed and DM incidence in Japanese older adults over 4.16 years of follow-up, and found significant association [ 30 ]. However, the mean gait speed was higher in that study (1.48 m/s) than in our study (1.32 m/s).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results also showed that slower gait speed (<1.32 m/s) was a significant predictor for incident DM in this population. These results were consistent with a previous study that examined baseline gait speed and DM incidence in Japanese older adults over 4.16 years of follow-up, and found significant association [ 30 ]. However, the mean gait speed was higher in that study (1.48 m/s) than in our study (1.32 m/s).…”
Section: Discussionsupporting
confidence: 93%
“…However, this study was a cross-sectional design that did not account for longitudinal analysis of gait speed and DM and OA. Only one study examined baseline gait speed and DM incidence in Japanese older adults over 4.16 years of follow-up [ 30 ]. Although this study found significant association between baseline gait speed and DM incidence, this study has some limitations such as small sample (n = 102), indicating underpower design that cannot be generalized, shorter time of follow-up affecting DM incidence capture, and included only healthy older adults who participated in an exercise program for nine years.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with type 2 DM have higher risk to develop plantar ulceration than normal population [8] [9]. There are two basic factors leading to ulceration among these patients which are neuropathy and increased plantar pressure values [10] [11].…”
mentioning
confidence: 99%